OMC et droit de la concurrence : le droit de l'OMC face au défi de la mondialisation des pratiques anticoncurrentielles et des opérations de concentration - Ndiaye, Djibril (Aix-Marseille Université, 2015)
En tant qu’organisation qui a vocation à réguler les échanges commerciaux mondiaux et qui promeut le libre-échange, l’OMC désigne naturellement l’une des principales, voire l’unique, structure internationale capable d’incarner l’approche multilatérale qui s’impose devant la mondialisation des pratiques anticoncurrentielles et des opérations de concentration. Les règles de concurrence présentes dans son corpus juridique, ainsi que la jurisprudence issue de leur mise en œuvre, grâce notamment à l’existence d’un mécanisme contraignant de règlement des différends, forment un droit primaire de la concurrence. Toutefois, un tel droit ne régit que les comportements des acteurs étatiques et n’appréhende les agissements des particuliers que de manière indirecte. Par conséquent, il nécessite d’être complété et adapté aux nouvelles réalités procédant de la mondialisation des économies, ce par le biais d’une adoption d’un accord multilatéral portant sur la concurrence. Le système de règlement des litiges devrait aussi subir une mutation, en renforçant ses techniques de sanction et en s’ouvrant aux personnes privées
Keywords: Accord multilatéral; Anti-Competitive practices; Comity; Commerce international; Competencia; Competition law; Concurrence; Concurrence (droit); Courtoisie; Dispute settlement body; Droit et mondialisation; Extraterritoriality; Extraterritorialité; Globalization; Mondialisation économique; Multilateral agreement over the competition; OMC; Organe de règlement des différends; Organisation mondiale du commerce; Pratiques anticoncurrentielles; WTO

Les conflits d'intérêts en arbitrage commercial international - Castres Saint Martin, Constance (Université Paris 2, 2015)
Le conflit d'intérêts est un sujet passionnant notamment en raison de son omniprésence dans l'actualité. Approximative, l'expression empruntée au magma lexical des politiciens et juristes anglo-américains s'est récemment diffusée en France dans le monde des affaires et aussitôt reprise par le jargon médiatique pour désigner des éventuelles interférences de l'intérêt privé dans l'exercice de pouvoirs de nature privée ou publique. Il n'existe en l'état actuel du droit positif français aucune réglementation spécifique de ces « conflits d'intérêts », pas plus en droit privé qu'en droit public, alors même qu'on se préoccupe de leur prévention tandis que leur sanction relève de qualifications plus générales. Il convient donc de s'interroger sur la définition et la valeur opératoire de cette notion et le régime juridique qui pourrait lui être réservé, ce que l'on se propose d'entreprendre dans la sphère du droit privé et par préférence dans le champ de l'arbitrage commercial, particulièrement exposé aux appétits hégémoniques des droits anglo-américains. Conflict of Interests is a fascinated subject due to its pervasiveness in the economic life. This approximated expression, borrowed from the politicians and Anglo-American lawyers' jargon, has recently spread into the French business world and was taken up by the media to designate the interferences of private interest in the exercise of powers of private or public nature. In the current state of French Law, there is no specific rule governing conflicts of interests, neither in Private Law, nor in Public Law. Indeed, politicians and scholars paradoxically only focus on their prevention, whereas their sanctions fall within the scope of broader notions. The aim of this research is to lay down the definition, the operative value and the regime of conflict of interests. The scope of this research shall be, within Private Law, Commercial Arbitration Law, which is particularly exposed to the hegemony of Anglo-American laws.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitral abuses; Arbitration; Confiance légitime (droit); Confidence principle; Conflict of interests; Conflit d'intérêts; Conflits d'intérêts; Disclosure; Due process; Dérives arbitrales; Impartiality; Impartialité; Independence; Indépendance; Issue conflict; Justice arbitrale (administration); Principe de confiance; Procès équitable; Révélation; Transparence; Transparency

The Modern Travelling Merchant: Mobile Communication in International Contract Law - Schroeter, Ulrich G. (Journal of Law, Society and Development, 2015)
The use of mobile communication devices such as mobile phones, smartphones, tablet computers or notebooks with access to the internet has become an everyday phenomenon in today's business world. However, whenever mobile communications are used for the purposes of contract formation, that is, the mobile dispatch of offers or acceptances, the mobility of the communicating parties raises important difficulties for the application of traditional legal rules: The fact that messages transmitted via phone, email or SMS can be dispatched and received Â at virtually any Â place on Â earth challenges the categories of private international law and international contract law, which are based on the (unspoken) assumption that parties communicate from their home country. The existing legal framework for cross-border contracts therefore hardly takes into account the possibility that parties may move across borders, and that the place of their communications may accordingly vary.The present article addresses the legal difficulties and uncertainties that crossÂ border Â mobile communication Â raises under international rules of law. It elaborates on the traditional role of the site of communication in this context before scrutinising how 'mobility friendly' the provisions Â of the relevant Â conventions Â developed Â by the United Nations, the Hague Conference for Private International Law and other organisations Â are. In doing Â so, Â it critically Â discusses Â in particular article 10(3) of the UN Electronic Communications Convention of 2005, the most recent attempt at regulating mobile communications. Finally, it identifies a number of problems that have hitherto been overlooked (as notably the interaction of article 10(3) of the UN Electronic Communications Convention with traditional private international law rules on the formal validity of contracts) and proposes appropriate solutions.
Keywords: Conflict of laws; Contract law; Electronic communication; Electronic contract formation; Mobile communication; Place of contracting; UN Electronic Communications Convention; m-commerce

BRICS and Sub-Saharan Africa Trade Interdependence and Peace: Evidence Based on Revealed Comparative Advantages - Beyene, Hailay Gebretinsae (Journal of Law, Society and Development, 2015)
This study examined economic integration through trade between BRIGS (Brazil, Russia, India, China and South Africa) countries and sub-Saharan Africa. The study examines the comparative advantages of the two economic blocks with respect to the exportation of merchandise (food, agricultural raw materials, fuels, ores and metals, and manufactures). The findings of this study reveal the actual status of these two regions as economic partners in each of the five subsectors of merchandise exports.The Â trend Â shows Â that, Â with Â the Â exception Â of Â manufactures Â exports, the competitiveness of all subsectors of the merchandise Â exports ofÂ BRIGS is characterised by a Â declining Â trend. Â BRIGS has Â a Â comparativeÂ advantage in the world in the exportation of manufactures and fuels, and comparative disadvantage in the export of food, agricultural raw materials, and ores and metals. Â Interestingly, manufactures are Â continuously Â and consistently Â in a steadily rising trend. This is evidence that BRIGS's structural transformation towards higher valued-added commodities is proceeding well, which means that policy makers should be considering ways of enhancing it further.In the case of sub-Saharan Africa,Â with the exception of manufactures exports, it is found to have comparative advantages in all merchandise exports. Sub- Saharan Africaâ€™s competitive advantage is the highest in the exportation of ores and metals, followed by fuels, agricultural raw materials and food. Sub-Saharan Africa has a comparative disadvantage in the export of manufactures throughout the period considered in this study. This implies that the prospects of structural transformation to downstream of the higher value-added commodities export part of the supply chain are good: the slow pace of transformation towards higher value-added goods should therefore be demanding the attention of policy makers. The study has revealed that sub-Saharan Africa is more competitive than BRICS in the exportation of ores and metals, fuel, agricultural raw materials and food. On the other hand, BRICS is more competitive than sub-Saharan Africa in the export of manufactures.The study has also revealed that significant economic integration can be sustained Â between Â BRICS Â and Â sub-Saharan Â Africa Â in Â the Â exportation Â of all merchandise subsectors. Specifically, sub-Saharan Africa is a potential destination market for BRICSâ€™s exports of manufactures. Conversely, BRICS is also a potential destination market for sub-Saharan Africaâ€™s exports of ores and metals, fuel, agricultural raw materials and food.Economic integration between BRICS and sub-Saharan Africa favourably influences peace and stability in the regions. Sustaining peace and stability in these regions also favourably influences the wellbeing of the communities.
Keywords: BRICS; Economic integration; Sub-Saharan Africa; merchandise exportation; peace and stability; revealed comparative advantage; structural transformation

CISG and Regional Sales Law: Friends or Foes? - Coetzee, Juana (Journal of Law, Society and Development, 2015)
Economic co-operation and integration brings with it a need to harmonise mechanisms for the regulation of international trade, not only at a public-law level between states but also at a private-law level between traders inter partes. It is often forgotten that differences in the substantive law applicable to a contract function as a non-tariff barrier to trade. Because international trade facilitates economic development, the focus in this article is on the harmonisation of sales laws. Traditionally, private law harmonisation has been conducted by international private or inter-state organisations that specialise in the harmonising of law at a global level. Today, private organisations and groups devoted to harmonising business laws, as well as regional economic integration organisations, are also pursuing legal harmonisation. Global, regional and domestic laws now all exist in the same area of the law, which can give rise to duplication of efforts and problems with the co-existence of global and regional sales law. This article will discuss these issues with reference to the United Nations Convention on Contracts for the International Sale of Goods (CISG) and selected regional laws in considering whether regional harmonisation can act as a stepping stone towards increased harmonisation at a global level or whether it is to be viewed as a threat to global integration and harmonisation.
Keywords: CESL; CISG; Global harmonisation; Harmonisation of sales laws; OHADA; PACL; SADC; regional harmonisation

Choice of the UNIDROIT Principles of international commercial contracts - Meer, Tiana Van der (University of Johannesburg, 2015)
LL.M. (International Commercial Law) The principle of party autonomy is a fundamental characteristic of private international law. The contracting parties’ freedom of choice regarding the law governing their contract is one which optimises the fundamental principle of party autonomy. It is generally accepted that a choice of a governing law by the parties should be respected by adjudicating bodies such as domestic courts and arbitral tribunals. It would often benefit contracting parties to choose a neutral legal system so that there will be a “fair playing field” in case a dispute arises between them. However, some domestic legal systems and regional, supranational and international commercial instruments limit the choice of law to that of a recognised domestic legal system. Accordingly, choosing the UNIDROIT Principles on International Commercial Contracts as governing law will, in most cases, not be a viable option for the parties concerned. Such a limitation on the choice of a governing law does not promote the fundamental principle of party autonomy, which is characteristic of private international law. Parties to an international commercial contract should be able to choose a non-state system of law to govern their contract. The UNIDROIT Principles of International Commercial Contracts provide a comprehensive, complete and easily obtainable system of law compiled by legal experts in the various fields which form part of international commercial law. It follows a via media system of law with regards to Civil Law and Common Law legal systems. This paper will discuss the principle of party autonomy, as well as the possibility of a choice of non-state law, in particular the UNIDROIT Principles of International Commercial Contracts, as the law governing an international commercial contract. The choice of law will be discussed with reference to the position taken in domestic courts as well as that in international arbitration. To review the impact and success of the UNIDROIT Principles in the realm of international commercial contracting, various international commercial instruments will be discussed.

عقد الاعتماد الايجاري الدولي - عسالي, عبد الكريم (جامعة مولود معمري, 2015)
Keywords: Contrats; Convention UTAR de 1988; Crédit-bail international; Droit des testaments; اتفاقية اوتارا لسنة 1988; الاعتماد الايجاري الدولي; العقود; قانون الارادة

The Vienna Sales Convention and private international law - Wethmar-Lemmer, Marlene Muriel (University of Johannesburg, 2015)
The United Nations Convention on Contracts for the International Sale of Goods (the CISG or the Vienna Sales Convention) was adopted at a diplomatic conference of the United Nations held in Vienna during 1980. The Convention came into force on 1 January 1988. According to its preamble, the Convention is based on the premise that “the adoption of uniform rules which govern contracts for the international sale of goods and take into account the different social, economic and legal systems would contribute to the removal of legal barriers in international trade and promote the development of international trade”. The CISG has proven to be successful in its endeavour and currently has 74 member states representative of all legal traditions. As an international convention, the CISG has been lauded for its “simplicity, practicality and clarity”. Schlechtriem observed that the CISG has now gained worldwide acceptance. It has even been stated that the CISG has established a “world law on international sales” and that it has influenced several domestic sales laws. It is submitted that the CISG constitutes an important component of modern international commercial law or of the modern lex mercatoria. Therefore, a study that aims to establish a better understanding of the scope and functioning of the CISG and its relationship with domestic law, is of special relevance for the international business and legal community. The two basic methods of the unification of law, ie the unification of substantive law and the unification of private international law, have both been utilised in the field of the international sale of goods. The CISG is the most notable example of first mentioned method of unification.
Keywords: CISG; Choice of law clause; Conflict of laws; Contracts for the international sale of goods; Convention de Vienne; Export sales contracts; Lex mercatoria; Party autonomy; Sales; UNIDROIT Principles

Convergence of international trade and investment law in practice : how should investor-state arbitral tribunals engage with trade norms? - Chevry, Jonathan (European University Institute, 2015)
This thesis aims to provide an analytical framework to which investor-State arbitral tribunals can refer in cases where international trade law is invoked. The starting point of the present study is the trend in commentary on international trade and investment law, which makes the argument that international trade and investment law should be reconciled due to the clear "convergence" between (some of) their constitutive elements. This convergence argument is not misguided: there are similarities between the underlying principles of global trade and investment and, as such, a better coordination of these principles would be helpful for several reasons. Such reasons include legal certainty, reduction of transaction costs, better coherence in the operation of international agreements that now combine both trade and investment provisions, to name a few. However, no matter how reconcilable or converging the two disciplines may be, their enforcement mechanisms are structurally different and are likely to remain so even if the reforms towards a modernization of the investment dispute settlement (currently discussed at the EU policy level) are eventually implemented in the near future. In light of this last point, it is possible to claim that integration between trade law and investment law will only have limited or even negative effects if the trade and investment adjudicators continue to exercise their functions in an isolated manner, without taking cognizance of (i) the norms contained in the other discipline and (ii) the other adjudicator's scope of authority. Effective convergence of trade and investment entails a two-way process pursuant to which one adjudicator can use (i.e. take into account, refer to, apply, interpret and enforce) the law of the other and vice-versa. The thesis envisages one of the two dimensions of this process, namely the use of trade law by the investment adjudicator. Looking into the details of the convergence argument, the role of investment dispute settlement mechanism and the use of trade norms over the past two decades by litigants and arbitrators, the present study identifies both the legal techniques and obstacles these actors shall apply or go beyond in order to use trade norms in the most appropriate way and, more importantly, benefit from this use.
Accepted: 2015-12-09T14:30:56Z
Keywords: Arbitrage; Arbitragem; Arbitration; Foreign investment; Foreign trade regulation; International commercial arbitration

CISG and the freedom of form principle vs. reservations under Article 96 of the CISG - Pohl, Małgorzata (Transformacje Prawa Prywatnego, 2015)
This article aims to present the consequences of a state’s declaration to opt-out from the freedom of form principle, under article 96 of the united nations Convention on Con tracts for the international sale of goods 1980 (CISG). In practice, problems have developed as whether or not to apply the freedom of form when a contract is concluded between two business entities, where one has its place of business in an article 96 CISG reservation state, and the other does not. The issue concerning the reservation’s effects has led to the creation of “two schools of thought” established by the doctrine and case law in this respect. it is the author’s intention to present the proper methodology of the interpretation and application of articles 12 and 96 CISG bearing in mind the various opinions in this respect. In the author’s opinion, in such situations the court should follow the rules of private international law to seek an answer as to whether or not the obligation of written form applies. Some of the CISG Contracting states that currently maintain an article 96 Cisg dec laration, refrain from withdrawal of their declaration despite the fact that the prerequisites for such a reservation are no longer met, as their domestic legal systems do not impose a written form requirement, as was the case at the time when the Cisg was negotiated. In the author’s opinion, in cases where the rules of private international law point to the law of such a state, the courts should, in practice, refrain from following the article 96 Cisg reservation, i.e. no freedom of form, and should instead apply the less formal domestic law as to the form.

More than 25 years of the contracts for the international sale of goods (CISG): Rethinking the role of the CISG in the SADC region - Shumba, Tapiwa (Speculum Juris, 2015)
The Convention on Contracts for the International Sale of Goods (CISG) has proved popular, particularly outside Africa. However, only a few States have adopted it in Africa, with only two in the Southern African Development Community (SADC). Taking into account the role that African countries have played in the United Nations Commission on International Trade Law (UNCITRAL) and the creation of the CISG, it has always been pertinent to look at whether SADC Member States should adopt the CISG as an instrument for harmonising the law of international sales in the region. Since it came into force, only two SADC Member States (Lesotho and Zambia) have ratified the convention. There is apparent reluctance from the rest of SADC Member States to ratify the convention despite calls to that effect and the genuine need for legal harmonisation. The article revisits the call for the ratification of the CISG in SADC and considers other realistic alternatives to ratification.